1984
DOI: 10.1007/bf02013611
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of endemicProvidencia stuartii isolates from patients with urinary devices

Abstract: Providencia stuartii has emerged as a significant nosocomial urinary tract pathogen. An increase in the number of Providencia isolates from urine cultures prompted an investigation into the possibility of an outbreak due to this organism. A high proportion of patients studied had urinary devices. Four wards were screened at two time periods to ascertain the prevalence of Providencia stuartii in urine cultures. Biotype, serotype, antibiogram and plasmid content were determined for each Providencia isolate. Of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…stuartii were 0:25 and 0:52 (two occasions each), both of these serotypes have been reported as being amongst the six most common serotypes isolated in hospitals in Canada, USA and UK ). The same serotypes have also been reported from a more recent episode of nosocomial infection in the USA (Hollick et al 1984). There have been reports of only five different serotypes isolated from hospital patients in the UK, the second most commonly isolated serotype was 0:25, which was found in the calves studied by us Epidemiological Research Laboratory, 1977).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…stuartii were 0:25 and 0:52 (two occasions each), both of these serotypes have been reported as being amongst the six most common serotypes isolated in hospitals in Canada, USA and UK ). The same serotypes have also been reported from a more recent episode of nosocomial infection in the USA (Hollick et al 1984). There have been reports of only five different serotypes isolated from hospital patients in the UK, the second most commonly isolated serotype was 0:25, which was found in the calves studied by us Epidemiological Research Laboratory, 1977).…”
Section: Discussionsupporting
confidence: 54%
“…stuartii. (Hawkey, Bennet & Hawkey, 1984;Hollick et al 1984). Thus although plasmid profiles may be useful epidemiological markers, considerable care is required in using them to interpret the movement of strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of infections by P. stuartii is complicated by its intrinsically strong resistance to a wide range of antibiotics (4,(6)(7)(8) and by its ability to form biofilms. The latter may attach and grow on indwelling catheters (3,9,10) and on uroepithelial cells (11). Recently, we reported the microscopic characterization of P. stuartii plankton and biofilms and the unexpected finding that this species forms floating communities of cells in solution before its deposition as a surfaceattached biofilm (12).…”
mentioning
confidence: 99%
“…1973, G218, p. 62) reported that the ability to ferment lactose and degrade urea could be transferred from Proteus rettgeri (now Providencia rettgeri) to Escherichia coli and Salmonella species and that the "Proteus" strain could spontaneously and irreversibly lose urease activity. Several other reports described the instability of the urease trait in P. stuartii (3,14), and conjugative transfer of urease in P. stuartii was later demonstrated by Grant et al (4) and was correlated with the presence of a high-molecular-weight plasmid by Hollick et al (9). P. stuartii is commonly resistant to many clinically useful antibiotics.…”
mentioning
confidence: 95%